Comparative study of in‐vitro autofluorescence of normal versus non‐melanoma‐skin‐cancer cells at different excitation wavelengths. Issue 5 (25th January 2023) - Garbarino, Federico; Scelfo, Daniel; Paulone, Gabriele; Paganelli, Alessia; Ulrici, Alessandro; Magnoni, Cristina; Pasquali, Luca
Abstract: In this experimental study the autofluorescence of squamous carcinoma cells, stimulated by 6 different excitation wavelengths in the range 280–533 nm, has been compared with the autofluorescence of normal control keratinocytes. Skin cells were cultivated in vitro, to isolate their characteristic autofluorescence form the more complex one that would be originated by the complete skin tissue. Autofluorescence spectra in the visible range were complemented by absorption measurements. It was observed that the control cells showed characteristic emission (and absorption) structures due to typical endogenous chromophores [FAD and NAD(P)H, lipo‐pigments, porphyrins], that were severely dumped in pathological cells. The autofluorescence spectra were then elaborated by multivariate analysis: after a first exploratory data analysis by means of Principal Component Analysis, the whole dataset was used to develop classification models using partial least squares‐discriminant analysis, to differentiate between normal and pathological cells. This permitted us to identify the most suitable fluorescence spectral interval, in the 550–670 nm range, to discriminate between normal and pathological behavior, independently on the excitation wavelength. Abstract : Autofluorescence spectra of squamous carcinoma cells and normal control keratinocytes are compared. Multivariate analysis is used to unambiguously discriminate between tumoral and normal cells. Cancerous cells show a drastic reduction of luminescence compared to healthy cells. A spectral region between 550 and 670 nm is identified that best discriminates between the two families.